PERENCANAAN JADWAL PENGADAAN RAW MATERIAL ADITIVE DENGAN METODE MATERIAL REQUIREMENT PLANNING (STUDI KASUS PT SGB) - Santoso, Priyono Budi; Awaludin, Asyik; Prayogi, Ahmad Said (Jurnal Sains Ilmu Teknologi Industri, 2022)
PT.SGB is a new factory that will operate. So that maximum efforts are needed in optimizing when the factory is in production and in the future. These efforts include increasing the effectiveness of the procurement of materials to be used. During the cement production process, several additive materials were purchased from third party vendors, including gypsum, fly ash and pozzolan (PT.SGB, 2021 With the MRP, the accuracy of the amount and timing of materials will ensure that the company's activities are effective and efficient. October amounted to 15,344 tons, while May amounted to 7,672 tons, and in November and December amounted to 18,412. while the gypsum material in December 20021 to March 2022, and also May to September 2022 amounted to 5,834 tons, while April was 2,912 tons, and in October and November 2022 amounted to 6,989 tons. For fly ash in December 20021 to March 2022, and also May to September 2022 amounted to 3,662 tons, while April amounted to 1,831 tons, and in October and November 2022 amounted to 4,394 tons. And for pozzolan in December 20021 to March 2022, and also May to September 2022 amounted to 2,929 tons, while April amounted to 1,465 tons, and in October and November 2022 amounted to 3,515 tons.